Complete Percutaneous Management of Lutembacher Syndrome with Severe Pulmonary Hypertension in a Middle Aged Indian Female: Is this the Magic Wand? - S Singh; SK Datta; KK Sethi; M Fotedar (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
Lutembacher syndrome is a combination of ostium secundum atrial septal defect with acquired rheumatic mitral stenosis. This is a case of middle aged woman who had lutembacher syndrome with severe pulmonary hypertension with class IV symptoms. She had very severe mitral stenosis with valve area of 0.7 cm2 and ostium secundum atrial septal defect of 14 mm size. The management of lutembacher syndrome was only surgical till 1990s. Total percutaneous management has been described in late 1990s. Percutaneous management is relatively cheaper option and saves the patient from artificial valve and related complications. However, only a small number of cases of total percutaneous management of this condition are available in world literature.  This patient was managed with percutaneous transmitral commissurotomy with Inoue balloon. Immediately after commissurotomy, her pulmonary artery pressure decreased by one-third. Device closure was done for her atrial septal defect in the same sitting. Her pulmonary artery pressure decreased further. The procedure was successful without any complications. She was symptomatically better on first post-procedure visit.